86.7k views
14 votes
6. 3x2 – 2x = 5
Quadratic formula

User Native
by
5.5k points

1 Answer

2 votes

Answer:

The solution to the quadratic equation be:


x=(5)/(3),\:x=-1

Explanation:

Given the expression

3x² – 2x = 5

Solving with the quadratic formula


3x^2-2x=5

subtract 5 from both sides


3x^2-2x-5=5-5

Simplify


3x^2-2x-5=0

For a quadratic equation of the form ax²+bx+c=0


x_(1,\:2)=(-b\pm √(b^2-4ac))/(2a)

For a = 3, b = -2, c = -5


x_(1,\:2)=(-\left(-2\right)\pm √(\left(-2\right)^2-4\cdot \:3\left(-5\right)))/(2\cdot \:3)


x_(1,\:2)=(-\left(-2\right)\pm \:8)/(2\cdot \:3)

Separate the solutions


x_1=(-\left(-2\right)+8)/(2\cdot \:3),\:x_2=(-\left(-2\right)-8)/(2\cdot \:3)

solving


x_1=(-\left(-2\right)+8)/(2\cdot \:3)


=(2+8)/(2\cdot \:3)


=(10)/(6)


=(5)/(3)

also solving


x_2=(-\left(-2\right)-8)/(2\cdot \:3)


=(2-8)/(2\cdot \:3)


=(-6)/(2\cdot \:3)


=(-6)/(6)


=-(6)/(6)


=-1

Therefore, the solution to the quadratic equation be:


x=(5)/(3),\:x=-1

User MatBos
by
5.2k points